Roads to decolonisation an introduction to thought from the global South - Duvenage, Amy. (New York, NY : Routledge, 2024)
Roads to Decolonisation: An Introduction to Thought from the Global South is an accessible new textbook that provides undergraduate students with a vital introduction to theory from the Global South and key issues of social justice, arming them with the tools to theorise and explain the social world away from dominant Global North perspectives. Arranged in four parts, it examines key thinkers, activists and theory-work from the Global South; theoretical concepts and socio-historical conditions associated with 'race' and racism, gender and sexuality, identity and (un)belonging in a globalised world and decolonisation and education; challenges to dominant Euro-American perspectives on key social justice issues, linking decolonial discourses to contemporary case studies. Each chapter offers an overview of key thinkers and activists whose work engages with social justice issues, many of whom are under-represented or left out of undergraduate humanities and social sciences textbooks in the North. This is essential reading for students of the humanities and social sciences worldwide, as well as scholars keen to embed Southern thought in their curricula and pedagogical practice.
Keywords: Decolonization -- Developing countries; Social justice -- Developing countries; SOCIAL SCIENCE / General